ANALISIS PEMASARAN KOPRA DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Moh Akbar; Effendy Effendy; Wirahatmi Wirahatmi (Universitas Tadulako, 2022)
This study aims to analyze the cocoa marketing chain from Labuan Toposo Village, Labuan Subdistrict, Donggala Regency to the hands of consumers. This research was conducted in Labuan Toposo Village, Labuan Subdistrict, Donggala Regency from March to May 2020. Respondents were determined using simple random sampling method (Simple Random Sampling) with 32 producers (farmers) as respondents and the trader respondents were selected by means of the Tracing Sampling method in order to obtain 1 trader and 1 wholesaler. marketing shows that the copra marketing channel in Labuan Toposo Village is through two marketing channels, namely: Farmers Traders, Collectors, Factory wholesalers (final consumers), Farmers, Factory wholesalers (final consumers). The results of channel 1 copra marketing margin analysis, namely MT = Rp. 1,500 / kg while the second channel is MT = Rp. 1,000 / kg. The share of the price received by cocoa farmers on channel 1 is 81.3%, while in the second channel is 87.5%. Marketing efficiency in the first channel is 9.0 %, while the efficiency value for channel II is 7.8%, so that of the two channels, the most efficient channel is the second channel with